Implication of field abandonment cost towards the economics of marginal field in Malaysia - Lam Kien Xhing, 1989- author; Razif Abd. Razak, supervisor; Fakulti Kejuruteraan Petroleum dan Kejuruteraan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper Sarjana Muda Kejuruteraan (Petroleum) - Universiti Teknologi Malaysia, 2012